Missed treatment in an Italian HBV infected patients cohort: HBV RER. Issue 11 (November 2016) - ,; Ferrari, C.; Giuberti, T.; Villa, E.; Andreone, P.; Pietrangelo, A.; Abbati, G.; Magnani, G.; Massari, M.; Verucchi, G.; Cancellieri, C.; Ricca Rosellini, S.; et al.
Abstract: Background and aims: Very little is known about the access to treatment for Chronic Hepatitis B in the real clinical practice and the characteristics of the patients who do not receive antiviral therapy. Methods: HBV-RER is an observational multicenter network that collected data of patients with HBV infection during a 3 years observational period (2009–2012). Results: Among 2527 HBsAg positive patients, 1099 were never treated (NT); only 280 were included in the analysis due to different exclusion causes A minority was HBeAg-positive. The median age was 42. At liver biopsy most patients had Metavir score of F0-F1. Univariate analysis between 280 NT patients and the 290 naïve to treatment showed that NT patients were mostly female ( P = 0.002), not Italian ( P = 0.044), younger ( P < 0.001). Metavir score was lower in NT (P0.002), such as the Fib4 score ( P < 0.001). HBV DNA level was significantly higher in NT. At multivariate analysis, independent variables associated with no-treatment were younger age, female gender, Metavir score F0-F1, Fib4 lower than 1.6 and lower blood level of HBV-DNA. Conclusions: There is a large number of patients eligible to treatment who do not receive it. A younger age and a less severe disease seem to be associated to deferral of treatment.